Kewenangan Notaris Dalam Persoalanpenyuluhan Hukum Dan Mediasi - Cindarputera, Ranggapandu; Putra, Mohamad Fajri Mekka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Notary have the authority to provide legal advice to ensure the legal security of a case. Morality, foundation, and foresight are the most important factors in understanding the abuse of power at the expense of others. Notaries are not given legal advice by the government, so there are notaries who have litigation and arbitrators. The purpose of writing is to clarify the legal consequences of an action that has not been sanctioned by the court, to clarify the legal consequences in the context of mediation. This study uses normative legal methods and uses primary, secondary, and tertiary legal materials. Data were collected using a literature survey, interview-style field survey, and valid material processing techniques, and quality material analysis was carried out. The findings show that a notary acting as a mediator is not legally responsible because the mediator is a neutral and impartial third party. Notaries are not required to be a mediator. The mediator is an authority and not a government official and does not administer the state. BUMN/D, as well as religious norms, dignity/relevance of the profession that can affect the honor of a notary.